Analysis of Sexual Education Knowledge in Children of Elementary School - Syifa Delaneira Oktora; Heri Yusuf Muslihin; Elan Elan (JURNAL PENDIDIKAN IPS, 2023)
ex education in Indonesia is still controversial, there are still many members of society who do not approve of sex education at home or at school. In general, society's view of sex education is something that is considered "taboo" to talk about with children, especially early childhood. People think that there will be a time when they will understand it naturally. Sex education that is not given at an early age results in high leve’ls of sexual violence against children by those closest to the child, including the family. The aim of this community service is to provide an understanding of sex education to children. The implementation of community service activities is carried out at elementary schools in the Sukaraja sub-district with participants taken from grades V and VI. The method used is lectures and questions and answers, with the media used LCD projectors and leaflets. The results of the implementation of this community service activity from the participants in class V and VI students who attended looked very enthusiastic, after the questionnaires before and after giving health education regarding sex education there appeared to be an increase in knowledge. The implementation of providing health education regarding sex education to increase knowledge for elementary school students in the Sukaraja sub-district with risks that might occur with the condition of the community really needs to be done, apart from being an addition and enhancing knowledge as well as an act to reduce the risk of child sexual abuse.